Developing cure kinetics models for interleaf particle toughened epoxies - Kratz, James; Mesogitis, Tassos; Skordos, Alexandros A.; Hamerton, Ian; Partridge, Ivana K. (SAMPE - Society for the Advancement of Material and Process Engineering, 2016)
In this study, we investigated the cure kinetics behaviour of the commercial Hexply® M21 thermoplastic interleaf epoxy resin system. Dynamic, isothermal, and cure interrupted modulated differential scanning calorimetry (mDSC) tests were used to measure the heat flow of the system, and semi-empirical models were fitted to the data. The cure kinetics model describes the cure rate satisfactorily, under both dynamic heating and isothermal conditions. The glass transition temperature was described using the DiBenedetto equation and showed that heating rate can influence formation of the network; therefore cure schedule must be controlled carefully during processing.